Therapeutic Jurisprudence and Restorative Justice in the United States: The Process of Institutionalization and the Roles of Judges - Traguetto, Jessica (International journal of offender therapy and comparative criminology, 2019)
The legal systems and the judiciary in many countries have been changed and reformed, with the aim of dispensing justice quicker and more effectively. Some reforms have tried a less adversarial approach to resolving legal disputes, for example, Therapeutic Jurisprudence (TJ) and Restorative Justice (RJ). The objective of this article is to describe how institutionalized these movements are in the United States and the roles played by judges in this process. The data collection involved document analysis, observation of court-hearings, and interviews with 13 judges from several judicial areas involved in TJ and/or RJ judicial proceedings in the United States. Data analysis was undertaken using content analysis and the software NVivo. The results provide evidence that (a) these movements are in a process of divergent change implementation; (b) judges who engage with these approaches act as institutional entrepreneurs; and (c) the judges interviewed can be classified into four roles that are complementary in the promotion of TJ/RJ: promoter, author, convener, and maintainer.